KEPEMIMPINAN TRANSFORMASIONAL DI SMP PENGUDI LUHUR SANTO ALBERTUS KETAPANG - Anastasia Anastasia; Usman Radiana; Fadillah Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aimed to determine the transformational leadership of principals as managers, motivators, and supervisors of innovators at SMP Pangudi Luhur Ketapang. The form of this research was conducted with a qualitative descriptive approach. The subjects were personnel of SMP Pangudi Luhur Santo Albertus Ketapang, principal, four teachers, Administration, Chairman of the committee, from the age of twenty-nine years to forty-six years, four boys, three girls. Methods of data collection were interviews, observation, documentation and analysis through data reduction, data presentation. The results of the study were 1) transformational leadership of the principal as a manager, namely having the principal's work program, teachers and school activity programs which are socialized during teacher meetings, all programs are implemented because of the collaboration between school heads and teachers 2) As the principal's motivator, giving encouragement, encouragement and praise for teachers who carry out their duties at school, rewards, rewards for teachers who are disciplined and achieving, 3) as supervisors principals carry out supervision to assess teacher performance, provide guidance to teachers to become professional educators. 4) As an Innovator, namely the principal looking for new ideas to create a change in the school        Keywords: Transformational Leadership of a School Principal